RANCANGAN SISTEM INFORMASI SUMBER DAYA MANUSIA MENGGUNAKAN METODE BERORIENTASI OBJEK (Studi Kasus: Penilaian Kinerja Dosen Universitas Bina Darma) - Sopiah, Nyimas; Nasir, Muhammad (Universitas Bina Darma, 2012)
This research was done at the University of Bina Darma Palembang. The purpose of this research is to help Bina Darma University in control valuation for lecturerâs performance . Training and Valuation Lecturerâs Performance Systems (KIDO) is expected to provide a sense of satisfaction and improve lecturerâs loyalty. UPMT Team (Integrated Quality Assurance Unit) had difficulty in assessing lecturerâs performance because the data processing software is now less effective or are still many deficiencies, such as the report generated only for that time period, the report generated only for the lecturer, report must be archived back into Microsoft Excel, the value of lecturerâs performance (KIDO) from the previous period can not be seen, etc.. So the authors make the analysis and design to overcome these problems. Analysis and design of information systems using object-oriented method with the tools (the tool), Unified Modeling Language (UML). Keywords: Lecturerâs Performance, Object-Oriented Methods, Unified Modeling Language (UML)